PENGARUH BUDAYA KERJA DAN PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KARYAWAN PT. POS INDONESIA (PERSERO) KANTOR POS UNGARAN 50500 - Aries Setyowati; Sudharto Prawata Hadi; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2014)
. This research analyze the effect of working culture and good corporate governance practise against employee performance in PT. Pos Indonesia (Persero) Post Office of Ungaran 50500. The type of this research is explanatory research. Data collection techniques in this research were questionnaries, interviews, observation and literature study. The population that used in this research was the entire employee in PT. Pos Indonesia (Persero) Post Office of Ungaran 50500 amounts 55 employees. The data obtained were analyzed using validity test, reliability test, simple liniear regression, mutiple linear regression and hypothesis testing with t test and F test with SPSS 15. The result indicating that working culture (X1) and good corporate governance (X2) affecting the employee performance (Y), partially and simultaneously.